2016
DOI: 10.1007/s00021-016-0262-9
|View full text |Cite
|
Sign up to set email alerts
|

Mean Flow Velocities and Mass Transport for Equatorially-Trapped Water Waves with an Underlying Current

Abstract: In this paper we present an analysis of the mean flow velocities, and related mass transport, which are induced by certain equatorially-trapped water waves. In particular, we examine a recently-derived exact and explicit solution to the geophysical governing equations in the β-plane approximation at the equator which incorporates a constant underlying current.Mathematics Subject Classification. 76B15, 74G05, 86A05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…However, as the form of (2.2) is explicit in terms of Lagrangian variables, it transpires that the solution (2.2) is quite amenable to an analysis of its mean flow velocities and related mass transport [19,59]. The presence of a constant underlying current term is a significant complicating factor for the analysis of (2.2), undertaken in [46], and this is what we describe briefly.…”
Section: Mean Flow Propertiesmentioning
confidence: 98%
See 3 more Smart Citations
“…However, as the form of (2.2) is explicit in terms of Lagrangian variables, it transpires that the solution (2.2) is quite amenable to an analysis of its mean flow velocities and related mass transport [19,59]. The presence of a constant underlying current term is a significant complicating factor for the analysis of (2.2), undertaken in [46], and this is what we describe briefly.…”
Section: Mean Flow Propertiesmentioning
confidence: 98%
“…where we denote by r = R(q − ct; s * , z 0 ) the functional relationship induced by relation (5.2) between the otherwise independent variables r and q, as follows from the implicit function theorem. In [46], it is shown that the mean Eulerian velocity is given by the relation That the mean Eulerian flow is westward for an adverse current is not surprising, because in the absence of the current, the mean Eulerian flow is westward in any case (cf. [59]).…”
Section: Mean Flow Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant motivation for this interest has been the fact that such waves have an exact description in a variety of settings in the form of equatorially trapped Gerstner like solutions, see [23] for a review of three-dimensional Gerstner like solutions in the equatorial region. Equatorially trapped surface waves have been investigated in [7,13,14] while surface waves in the presence of underlying currents have been treated in [22,25]. Internal geophysical flows are investigated in [10,4,33,32,36,27], while instabilities in such flows are addressed in [12,26,18,24].…”
mentioning
confidence: 99%